Generalised long duration probable maximum precipitation (PMP) isohyetal map for Peninsular Malaysia - Mamun, Abdullah Al; Hashim, Alias (American Spatial Hydrology Union, Inc (ASHU), 2004)
Isohyetal maps were prepared to estimate Probable Maximum Precipitation (PMP) for long duration storms in Peninsular Malaysia. Historical storms of 1, 3 and 5-day durations from 21 rainfall recording stations operated by Malaysian Meteorological Service (MMS) were identified and analysed to calculate the PMP vales. Maximum rainfall for 1, 3 and 5-day storms in the Peninsula were recorded as 809, 1272.9 and 1494 mm, respectively. The widely used and most reliable hydrometeorological method was used to derive and transpose the PMP values from the storm locations to all MMS stations in the Peninsula. Maximum transposed PMP for a particular duration was obtained for six selected historical storms.